FcγRIIb expression in early stage chronic lymphocytic leukemia. Issue 11 (2nd November 2017) - Bosch, Rosa; Mora, Alba; Vicente, Eva Puy; Ferrer, Gerardo; Jansà, Sonia; Damle, Rajendra; Gorlatov, Sergey; Rai, Kanti; Montserrat, Emili; Nomdedeu, Josep; Pratcorona, Marta; Blanco, Laura; et al.
Abstract: In normal B-cells, B-cell antigen receptor (BCR) signaling can be negatively regulated by the low-affinity receptor FcγRIIb (CD32b). To better understand the role of FcγRIIb in chronic lymphocytic leukemia (CLL), we correlated its expression on 155 samples from newly-diagnosed Binet A patients with clinical characteristics and outcome. FcγRIIb expression was similar in normal B-cells and leukemic cells, this being heterogenous among patients and within CLL clones. FcγRIIb expression did not correlate with well known prognostic markers [disease stage, serum beta-2 microglobulin (B2M), IGHV mutational status, expression of ZAP-70 and CD38, and cytogenetics] except for a weak concordance with CD49d. Moreover, patients with low FcγRIIb expression (69/155, 44.5%) required therapy earlier than those with high FcγRIIb expression (86/155, 55.5%) (median 151.4 months vs. not reached; p =.071). These results encourage further investigation on the role of FcγRIIb in CLL biology and prognostic significance in larger series of patients.